1996
DOI: 10.3171/jns.1996.84.5.0748
|View full text |Cite
|
Sign up to set email alerts
|

Surgery versus radiosurgery in the treatment of brain metastasis

Abstract: Surgery and radiosurgery are effective treatment modalities for brain metastasis. To compare the results of these treatment modalities, the authors followed 13 patients treated by radiosurgery and 62 patients treated by surgery who were retrospectively matched. Patients were matched according to the following criteria: histological characteristics of the primary tumor, extent of systemic disease, preoperative Karnofsky Performance Scale score, time to brain metastasis, number of brain metastases, and patient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
126
0
10

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 295 publications
(144 citation statements)
references
References 21 publications
8
126
0
10
Order By: Relevance
“…Similar general findings have been noted in prospective trials of WBRT, alone or with SRS, 8,13 in retrospective trials, 5,7,10,11 and in retrospective surgical series. 16 In the current series, only the number of brain metastases (single vs multiple) was found to be an independent prognostic factor of survival.…”
Section: Discussionmentioning
confidence: 95%
“…Similar general findings have been noted in prospective trials of WBRT, alone or with SRS, 8,13 in retrospective trials, 5,7,10,11 and in retrospective surgical series. 16 In the current series, only the number of brain metastases (single vs multiple) was found to be an independent prognostic factor of survival.…”
Section: Discussionmentioning
confidence: 95%
“…Studies are conflicting regarding the use of SRS in groups of brain metastasis patients with differing primaries. Bindal et al 21 noted a significant survival benefit for patients treated with surgical resection compared with SRS, while Auchter et al 22 concluded that SRS was as efficacious as resection. In yet a third study, Muacevic et al 23 found no marked difference in survival.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of brain metastases is often multimodal, with surgery, whole-brain radiotherapy (WBRT), stereotactic radiosurgery, and chemotherapy all playing a role (18,19). The selection of specific modalities of treatment is dependent on patientspecific factors, such as number, size, and location of metastases, patient's overall health and prognosis, and degree of symptoms attributable to these metastases.…”
mentioning
confidence: 99%